Sex-Change Chemicals and their Influence on the Brain - Catherine A. Harris (The Scientific World Journal)
The potential for man-made chemicals to mimic or antagonise natural hormones is a controversial issue, but one for which increasing amounts of evidence are being gathered worldwide. The controversy surrounds not so much the matter of whether these chemicals can mimic hormones in vitro — this phenomenon has been widely accepted in the scientific world — but more whether, as a result, they can disrupt reproduction in a wildlife situation. It has, nevertheless, been acknowledged that many wildlife populations are exhibiting reproductive and/or developmental abnormalities such as intersex gonads in wild roach populations in the U.K.[1] and various reproductive disorders in alligators in Lake Apopka, Florida[2]. However, the causative agents for many of these effects are difficult to specify, due to the extensive mixtures of chemicals — each of which may act via different pathways — to which wild populations are exposed, together with the wide variability observed even in natural (uncontaminated) habitats. As a result, any information detailing fundamental mechanism of action of the so-called endocrine disrupting chemicals (EDCs) is of use in determining whether or not these chemicals, as they are present in the environment, may in fact be capable of causing some of the effects observed in wildlife over recent years.